Development of a New Index to Assess Small Bowel Inflammation Severity in Crohn's Disease Using Magnetic Resonance Enterography. Issue 1 (5th February 2022) - Bouhnik, Yoram; Le Berre, Catherine; Zappa, Magaly; Lewin, Maïté; Boudiaf, Mourad; Zagdanski, Anne Marie; Frampas, Eric; Oudjit, Ammar; Scotto, Béatrice; Tissier, Muriel; Annet, Laurence; Aufort, Sophie; et al.
Abstract: Background: The severity of small bowel (SB) inflammation in Crohn's disease (CD) patients is a key component of the therapeutic choice. We aimed to develop a SB-CD Magnetic Resonance Enterography (MRE) index of Inflammation Severity (CDMRIS). Methods: Each gastroenterologist/radiologist pair in 13 centers selected MREs from 6 patients with SB-CD stratified on their perceived MRE inflammation severity. The 78 blinded MREs were allocated through balanced incomplete block design per severity stratum to these 13 pairs for rating the presence/severity of 13 preselected items for each SB 20-cm diseased segment. Global inflammation severity was evaluated using a 100-cm visual analog scale. Reproducibility of recorded items was evaluated. The CDMRIS was determined through linear mixed modeling as a combination of the numbers of segments with lesions highly correlated to global inflammation severity. Results: Four hundred and forty-two readings were available. Global inflammation severity mean ± SD was 21.0 ± 16.2. The independent predictors explaining 54% of the global inflammation severity variance were the numbers of segments with T1 mild–moderate and severe intensity of enhancement, deep ulceration without fistula, comb sign, fistula, and abscess. Unbiased correlation between CDMRIS and global inflammation severity was 0.76. Conclusions: The CDMRIS is now available to evaluate the severity of SB-CD inflammation. External validation and sensitivity-to-change are mandatory next steps. Lay Summary: Small bowel inflammation in Crohn's disease (CD) patients is a key component of the therapeutic choice. We developed a Magnetic Resonance Enterography (MRE) index of Inflammation Severity (CDMRIS) based on intensity of enhancement, deep ulceration, comb sign, fistula, and abscess.